Development of Interactive Organic Chemistry E-Module Using Macromedia Flash Improves Concept Mastery - Manurung, Hisar Marulitua; Simaremare, Juni Agus (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This study was examining to produce e-modules as teaching materials in interactive organic chemistry courses using macromedia flash through the development process and determine the effect of interactive organic chemistry e-modules using macromedia flash on student concept mastery. This research method is development research known as Research and Development (R & D) Borg and Gall model with the following research stages, 1) Preliminary Study, 2) Planning, 3) Initial product development, 4) Small-scale field test, 5 ) Revision of small-scale field test results, 6) Main field test, 7) Revision of main field test results, 8) Operational field test, 9) Final product revision, and 10) Product implementation. The research instrument was a questionnaire with 33 statements and a multiple choice written test with 20 questions. The instrument was used to measure the category of interactive organic chemistry e-module interpretation using macromedia flash through the development stages using a questionnaire based on language, material and media aspects and to measure students' conceptual mastery using a multiple-choice written test. Based on the results of the study, it was found that the interactive organic chemistry e-module using macromedia flash through the development stages was in the very good category with a score of 3.6. The hypothesis test of this research was obtained that the value of sig (2-tailed) was 0.000 < 0.05, this means that there is an effect of implementing an interactive organic chemistry e-module using macromedia flash as a result of development on concept mastery. The amount of increase that occurs in the mastery of students' concepts is 66.74%.